FAST TRACK LEGISLATION WITHOUT A LEGAL TRACK: A COMPARATIVE CRITIQUE OF ACCELERATED LAW-MAKING IN INDONESIA AND OTHER JURISDICTIONS - Kaharuddin Kaharuddin; Oemar Moechthar; Agus Sekarmadji; Dinar Karunia; Dwi Rahayu Kristianti; Ekawestri Prajwalita Widianti; Ave Maria Frisa Katherina; Yogi Hidayat (Diponegoro Law Review, 2025)
This study critically examines the trend of "fast-track legislation" in Indonesia, particularly focusing on the Omnibus Law on Job Creation, the IKN Law, and the 2024 Constitutional Court Law. While fast-track legislation is often used as a tool for crisis management, Indonesia’s approach raises significant concerns due to its lack of a formal procedural framework. Unlike mature democracies such as the United Kingdom, the United States, and New Zealand, which have regulated systems for expedited law-making, Indonesia’s fast-track process is largely unregulated and accelerates policy changes without proper public scrutiny. The study uncovers a troubling pattern where speed becomes a substitute for thorough deliberation, leading to a democratic deficit and allowing executive power to bypass essential checks and balances. By comparing Indonesia’s practices with those of established democracies, the research highlights that fast-track mechanisms can be effective when guided by clear legal standards, judicial review, and transparency. However, Indonesia’s current system risks undermining democratic accountability, as urgency is often used as a tool to avoid public participation and scrutiny. The article concludes by calling for the urgent codification of a transparent, participatory framework for expedited legislation within Indonesia’s existing legal structures. This framework should define criteria for urgency, ensure procedural safeguards, and prioritize public involvement, ultimately ensuring that the pursuit of speed does not come at the cost of democratic integrity.